Sosialisasi Platform Teknologi Informasi Sekolah Menengah Kejuruan Pusat Keunggulan di SMK Negeri 10 Bengkulu Utara - Yulia Darnita; Sastya Hendri Wibowo; Rozali Toyib; Muntahanah Muntahanah; Harry Witriyono (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
The problem faced by schools in managing grant funds or school Operational Assistance is that there is often a confusion of information related to fund management, from planning, budgeting and reporting processes, the school is often confused when facing challenges due to misinformation, there is no source of validated questions and answers and integrated schools can be trusted to answer school confusion regarding the management of BOS funds, the existing question and answer channels (Whatshap, telegram) are still not integrated, have not been verified and tracked, the process of finding answers that are not well communicated adds to the administrative burden of educators, Not yet available application to help teachers and students in the teaching and learning process. Service activities in the form of socialization, practice, question and answer and Focus Group Discussion related to the use of digital platforms aimed at reducing complexity, increasing efficiency, adding inspiration, and customized approaches related to the School Resource Platform, the Merdeka Teaching Platform and the Teacher: Learning Platform. This community service process can be expected so that participants as the Assistance Team from Higher Education are able to: 1) Explore the Merdeka Mengajar Platform and its various products from their Android-based devices / devices (including web-based information systems via computers, desktops or laptops) 2) Explain the functions and the benefits of the Teaching Device Product on the Merdeka Mengajar Platform 3) Explaining the functions and benefits of the Student Assessment Product on the Merdeka Mengajar Platform 4) To teachers as the main users of the Merdeka Mengajar Platform (and its various products) as well as other key users such as school principals and stakeholders other related activities and need ongoing activities because most participants still need other training to help the learning process lead to a digital system, online-based and independent learning.